The Foundation for Building the Conservation Capacity of Community Ecology - Crotty, Sinead M.; Altieri, Andrew H.; Bruno, John F.; Fischman, Hallie; Bertness, Mark D. (Frontiers in Marine Science, 2019)
Ecology is a young discipline that needs to develop into a predictive science to confront the challenges of human population pressure and habitat degradation. Basic ecology has disproportionately focused on undisturbed, charismatic ecosystems, species and academic questions, leaving gaps in its ability to inform the conservation and management of degraded, threatened ecosystems. Foundation species-dependent organisms have been studied at the expense of the habitat-forming species that build and maintain communities. We use cobble beaches as a model system to discuss the consequences of this disparity on translational ecology. We suggest that the historic development of ecology has led to an academic discipline ill suited for proactive conservation. We propose that the incorporation of foundation species and hierarchical organization theory into the conceptual framework of ecology will improve its predictive ability and successful application to conservation and the restoration of degraded ecosystems.